The Characteristics of Traffic Accidents (Case Study of Jendral Sudirman Street Metro City) - Mustaqima, Tazkia; Sulistyorini, Rahayu; Purba, Aleksander (Universitas Lampung, 2020)
A traffic accident is an accident on the road that is unintentional. One of them is Jendral Sudirman Street, a location where traffic accidents often occur because this road has a high traffic volume in Metro City. This research uses a qualitative method that is descriptive and tends to use analysis. The data collection is done by direct observation and measurement at the research location and obtained through existing data sources.Based on the analysis of data that has been done the number of accidents that occurred on Jendral Sudirman Street, namely 71 incidents from 2014-2018 of 465 incidents of accident in Metro City. Based on the characteristics of accidents most causes of accidents is due to human factors, the type of vehicle that has the most accidents is two-wheeled vehicles, the dominant type of accident is front-back accidents, the time of accidents that often occurs is the time interval 06.00-12.00 .Keywords: Traffic Accident, Characteristics of Accidents, Jendral Sudirman, Metro City